Dispositional goal orientation, beliefs about the causes of success and intrinsic satisfaction in young elite paddlers - Ruiz-Juan, F.; Gomez-Lopez, M.; Pappous, A.; Alacid Carceles, F.; Flores Allende, G. (Journal of Human Kinetics, 2010)
The purpose of this study was to primarily examine the psychometric properties of the castillan version of three commonly used psychological scales in sport (Perception of Success Questionnaire, Beliefs About the Causes of Sport Success Questionnaire and the Sport Satisfaction Instrument); secondly, to verify the degree of intrinsic satisfaction in a sample of young Spanish paddlers. The participants of this study were 209 elite paddlers classed in the junior category (13-4 years old). Results show that the Castilian versions of the questionnaires demonstrate acceptable validity and reliability in a sample of young paddlers. Athletes report high scores on perception of success oriented task scale, which is positively related with enjoyment and the attribution that success in sport depends on effort. This study also confirmed gender differences in questionnaire responses.